Literasi Pengisian E-SPT Tahunan Wajib Pajak Orang Pribadi Pada Jemaat HKBP Sutoyo - Lenny Panggabean; Jisman M Lubis; Swanto Sirait; Rudy S Sinaga; Daniel Kopong (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2022)
Tax notification letter, hereinafter abbreviated as SPT, is a letter used to report the tax obligations of every individual and corporate taxpayer, without exception. This is a polemic every year that is felt by every taxpayer, especially individual taxpayers, where the SPT could be manual but with the reforms in the field of taxation, taxpayers inevitably have to make adjustments. This raises a new problem where not all individual taxpayers are familiar with the world of digitalization. Therefore, this community service activity (PPM) is here to bridge the problems that occur around the introduction and filling of e-SPT in accordance with the provisions of the applicable laws and regulations. The method used in this PPM is to conduct webinar counseling with the consideration of the COVID-19 outbreak which is still high and the distribution of online questionnaires to find out what factors cause difficulties in filling out the annual e-SPT for individual taxpayers every year.